Comparison of the dynamic balance in youth male wrestlers according to age, body mass index, and participation level - Lima, Y. (Turkish Journal of Sport and Exercise, 2021)
The aim of this study was to evaluate the dynamic balance in youth wrestlers according to age, body mass index (BMI) and participation level. A total of 68 youth wrestlers participated in this study. They were subdivided according to participation levels (elite and sub-elite), age (13-14,15-16,17-18) and BMI (<20, 20-25, >25). The modified star excursion balance test (mSEBT) was performed by the same sports medicine specialist. All directional scores (anterior (A), posterior-lateral (PL), posterior-medial (PM)) and composite score (CS) on the dominant (p<0.001; p<0.001; p=0.002; p=0.001; respectively) and non-dominant sides (p<0.001; p=0.003; p=0.004; p<0.001; respectively) were higher in elite-level wrestlers compared to sub-elite ones. According to age, the dominant side`s A, PM scores and CS in 17-18 year-old wrestlers were higher compared to younger ones (p=0.003; p=0.01; p=0.009; respectively) and the non-dominant side`s all scores (A, PL, PM, CS) in 17-18 year-old wrestlers were higher compared to younger ones (p=0.001; p=0.003; p=0.007; p=0.001; respectively). According to BMI, the dominant side`s A, PL scores, and CS in wrestlers with a BMI < 20 were significantly lower compared to BMI > 20 (p=0.01; p=0.023; p=0.013; respectively). Dynamic balance in youth wrestlers may differ by age, BMI and level of participation. Balance measurements in youth wrestlers should be performed and necessary precautions should be taken to prevent sports injury and improve athletic performance.